Protective Effects of Autologous ‎Platelet-Rich Plasma (PRP) on the Outcome of ‎Cryopreservation in Rabbit Sperm: Autologous ‎Platelet-Rich Plasma (PRP) on the Outcome of ‎Cryopreservation - Abdulla, Alaa Kamil; Rebai, Tarek; Al-Delemi, Dhia Hussein Jassim (Cellular and Molecular Biology, 2022)
Sperm ‎cryopreservation is a cost-effective means of preserving gene resources and ‎transporting sperm across distant locations. However, due to the ‎general disadvantages of using freeze-thawed sperm, to prevent this irreversible damage, cryopreservation techniques must be ‎improved by the addition of additional cryoprotection agents. ‎This study aims to improve the freezability of buck semen using an ‎‎intratesticular injection of Autologous ‎Platelet-Rich Plasma (‎PRP) and ‎confirm this theory by Casa laboratory analysis and gene ‎expression detection of three genes (CATSPER1‎, SPAG5 and Hsp70). Twenty ‎rabbits a New ‎Zealand ‎healthy male were randomly ‎‎divided into two equal groups; ‎the control and PRP group ‎which enriched with PRP, ‎the semen ‎collection was ‎applied after 10 weeks, then each sample ‎was ‎divided into two ‎‎fractions; ‎First ‎‎fractions ‎‎ we apply the ‎ laboratory semen analysis ‎directly, and the second ‎‎fractions ‎‎were ‎ cryopreservation, then thawed after one ‎month to apply ‎‎the same ‎ laboratory analysis. The ‎results of CASA, DNA fragmentation, and‎ real ‎time-PCR analysis ‎had ‎ ‎‎statistically significant ‎differences (P<0.01) when compartment ‎of these values ‎after and ‎‎before freezing, yet we don’t ‎record any statistical ‎differences between the C group ‎and CR ‎group.‎ This study’s findings are extremely significant, indicating that intratesticular injection of PRP ‎ is a good method for using in enhancing the rabbit sperm procedure after ‎freeze-thawing.